Comparative effects of xylitol and erythritol on modulating blood glucose; inducing insulin secretion; reducing dyslipidemia and redox imbalance in a type 2 diabetes rat model - Nontokozo Z. Msomi; Ochuko L. Erukainure; Veronica F. Salau; Kolawole A. Olofinsan; Md. Shahidul Islam (Food Science and Human Wellness)
Xylitol and erythritol have been reported in numerous previous and recent studies as potential antidiabetic sweeteners, however, it is not certain which one is most effective in this regard. In the present study, the effects of xylitol and erythritol were comparatively investigated on blood glucose, insulin level, dyslipidemia, pancreatic islet morphology and β-cell function, and redox imbalance in a type 2 diabetes (T2D) model of rats. Seven-week-old male Sprague-Dawley rats were randomly divided into 8 groups: Normal Control (NC), Diabetic Control (DC), Diabetic Xylitol 5 % (DX5), Diabetic Xylitol 10 % (DX10), Diabetic Xylitol 20 % (DX20), Diabetic Erythritol 5 % (DE5), Diabetic Erythritol 10 % (DE10), and Diabetic Erythritol 20 % (DE20). T2D was induced in the diabetic groups initially by feeding 10 % fructose solution to induce insulin resistance followed by an intraperitoneal injection of streptozotocin (40 mg/kg body weight) dissolved in citrate buffer (pH 4.5) to induce partial pancreatic β-cells dysfunctions. The animals in NC group were fed with normal drinking water and injected with citrate buffer only. After the confirmation of diabetes, the xylitol and erythritol with above-mentioned concentrations were supplied to the respective animal groups when the animals in NC and DC groups were supplied with normal drinking water. After 8 weeks intervention period, the body weight, fluid and water intake, blood glucose, serum alanine aminotransferase, aspartate aminotransferase, CK-MB and creatinine were significantly decreased, while the serum insulin level, serum lipids, glucose tolerance ability, pancreatic islet morphology and β-cell function, pancreatic and serum redox imbalance were improved in the most xylitol and erythritol fed groups compared to the DC group, when effects were better for xylitol compared to erythritol. The data of this study suggest that xylitol has better antioxidant and antidiabetic effects compared to erythritol. Therefore, xylitol can be used as a preferrable dietary anti-diabetic sweetener or supplement over erythritol for the management of diabetes and its associated complications.